Pengaruh Kinerja Aparatur Desa Terhadap Kualitas Pelayanan Kepada Masyarakat di Desa Rantau Mapesai Kecamatan Rengat - Yenny Iskandar; Suharmiyati Suharmiyati; Reni Maralis (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research was conducted in Rantau Mapesai village. This research aims to determine the performance influence of village apparatus on the quality of service to the people in Rantau Village Mapesai Sub District Rengat District Indragiri upstream. The population is the total number of people in the region of Rantau Mapesai 993 in 2018 and for the number of samples taken are as many as 91 people. With data analysis used simple linear regression, F test, instrument test, and normality test. The results of the study can be seen that the performance of the village apparatus is very influential in the quality of service to the people in the village of Rantau, it is also supported by the village head assisted staff who are working to guide and control village governance. The presence of village apparatus in society is intended to foster passion, initiative and new ideas in order to improve the lives of its village society.